2019
DOI: 10.3892/mmr.2019.10746
|View full text |Cite
|
Sign up to set email alerts
|

Exopolysaccharide from Paecilomyces lilacinus modulates macrophage activities through the TLR4/NF‑κB/MAPK pathway

Abstract: Multiple exopolysaccharides (EPSs) have been isolated from various organisms in extreme environments and have yielded a variety of activities. The present study evaluated the immunomodulatory capabilities of an EPS (termed PH-EPS) derived from the fungus Paecilomyces lilacinus PH0016, which was isolated from a tropical and hyperhaline environment in southern China. The macrophage RAW 264.7 cell line was used to investigate the mechanism of PH-EPS-induced macrophage activation. The results indicated that RAW 26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…These MAPK‐associated pathways are participating in a major role in signal transduction, regulate the cytokine release and affect the multiple cell functions (Johnson & Lapadat, 2002). There are numerous studies have reported that polysaccharide and LPS can induce the phosphorylation of P38, JNK, ERK, cytokine, and NO‐releasing activities in activated RAW264.7 cells (He et al., 2019; Jones, Adcock, Ahmed, & Punchard, 2007; Yoon et al., 2004). Similarly, the RAW264.7 cells treated with WBP‐F enhance the phosphorylation of P38, JNK, ERK (Figure 4a‐d) and significantly increased the expression of proteins with increasing the concentration of WBP‐F.…”
Section: Resultsmentioning
confidence: 99%
“…These MAPK‐associated pathways are participating in a major role in signal transduction, regulate the cytokine release and affect the multiple cell functions (Johnson & Lapadat, 2002). There are numerous studies have reported that polysaccharide and LPS can induce the phosphorylation of P38, JNK, ERK, cytokine, and NO‐releasing activities in activated RAW264.7 cells (He et al., 2019; Jones, Adcock, Ahmed, & Punchard, 2007; Yoon et al., 2004). Similarly, the RAW264.7 cells treated with WBP‐F enhance the phosphorylation of P38, JNK, ERK (Figure 4a‐d) and significantly increased the expression of proteins with increasing the concentration of WBP‐F.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to hypoxia, various other factors, such as ROS and transition metals, can also regulate HIF1α activity (Chun et al, 2002;Ullah et al, 2017). It is well known that foreign antigen induces macrophage activation via stimulating TLR4/NFκB pathway (Zhang et al, 2015;He et al, 2019). Recent studies have shown there is an interaction between HIF1α and TLR4/NFκB signaling pathway, which induces macrophage activation (Rius et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The cytocompatibility of the EPS was evaluated on RAW264.7 murine macrophages and HaCaT human keratinocytes using the MTT method [ 38 ]. In brief, 5 × 10 3 cells/mL were seeded into a 96-well microplate and incubated at 37 °C for 24 h. Cells were then treated with different concentrations (50, 100, 500, and 1000 μg/mL) of the EPS for 24 h. Cells treated with only DMEM medium served as the control.…”
Section: Methodsmentioning
confidence: 99%